The «potestà correzionale» of the father in the second half of the 1800’s among the Sienese patriciate (Italian Review of Legal History, 2019)
This essay took inspiration from letters and notes of the Sienese patrician Celso Bargagli Stoffi found in the family’s archive (kept in Montefollonico (SI) and to be deposited to the State Archive of Siena), dating back to the second half of the 1800’s. In 1888, he realized that his 17 years old son, Antonio, had abandoned his studies and compromised himself with usurers, dancers and prostitutes. Hence, enforcing his “potestà correzionale”, he tried various strategies to induce him into changing his lifestyle.The abundance of documentation and the perspective from the city’s élite, that includes confrontation between relatives, friends, members of the institutions and lawmen, makes this single episode a “case study”. Although it can’t be generalized, this case offers the possibility of a detailed analysis of the matters relative to the control of undisciplined youth among a transforming provincial leading social class.Antonio, motherless from birth, grew up surrounded by the tenderness of his grandmothers, his aunts, his uncles and the German housekeeper, that made him a well-mannered but spoiled kid. When he turned 11, his father found it necessary for him to get an adequate education for the title of gentleman, and sent him to the well-known Jesuit school Stella matutina in Felkirch, Austria. The impact of the strict discipline and study system on him was traumatic and triggered in him rebellion against any authority. After two years, he managed to leave the school. His father gave up and brought him back to Italy, to put him in the Badia Fiesolana school that was managed by the more tolerant Piarist Fathers. During the course of a few years he deeply changed and, while living in Florence, got close to the wildest youth and started living a libertine and dissolute life.His father took action at the end of 1888. He brought him back to Siena to live together in the family mansion where he could better control him. But the kid kept wasting his life with wine, girls, sex and flings, assuming all the anti-social behaviors typical of adolescence: always disgruntled, victim of uncontrollable sexual appetites that led him to reckless behaviors, liar, touchy, hostile towards his father up to taunting him—bold and pretentious—he did not respect the social boundaries and flaunted confidentiality with people of lower class or low morality.No action from parents, friends, and lawyers managed to correct him, hence the father, as his last resort, in December 1890, asked to the President of the Court of Siena, on the basis of article 222 of the Civil Code, to confine him into a re-education and correction institute.This was only a threat because, in agreement with other Sienese nobles and members of the leading social class, he decided to force him to a long sea travel to Chile. The notables managed to avoid the application of a State law that would have brought social discredit to the group and came up with a nearly ad hoc sanction, made possible thanks to the personal relationships with the high institutional levels.The sanction did not include any punitive or re-educative action, but it had the objective of withdraw the young man from his lovers and his creditors to prevent him from creating more debts. Only the direct experience of the inconveniences and dangers he would have faced by living away from the family could convince him to change his lifestyle. Although he did not learned any specific lesson either during the four months spent on the ship or in Valparaiso, where the Consul treated him as a young man of respect. It is not known if Antonio actually repented of his misbehavior. In fact, he suffered from last stage phthisis and was rushed back to Italy, where he did not arrive alive. He died on the ship three days before reaching the port of Genoa in September 1891, at the age of 20. (trad. M. Vigni, V.Barra).
Keywords: Siena; Patriciate; Parental rights; Adolescence; 1865 Civil Code; XIX century